Determination of echocardiographic values in the medium-size Peruvian Hairless Dog - Ramírez Ríos, Flor de María (2022)
The Peruvian Hairless Dog (PHD) breed was registered in 1981 in the International Cinological Federation and is a National Heritage of the country. The breed has three defined sizes: large, medium and small. Echocardiographic reference values have been published for the general canine population; however, the clinical value is relative when considering the variation between breeds and their categories. The aim of this study was to determine the normal echocardiographic values of PHD according to age, weight and sex. The sample was 10 males and 20 females, comprising 17 young adults, 9 middle adults and 4 senior adults, and by body weight in 15 dogs ≥8-≤10 kg and 15 dogs >10-≤12 kg. Ten echocardiographic parameters were evaluated, which did not present significant differences by age group. The weight variable showed significant differences for the values LVDD (diastolic left ventricular diameter), LVSD (systolic interventricular septum diameter), LVPD (diastolic left ventricular wall diameter), DSVID (diastolic interventricular septal diameter) and DVDS (right ventricular diameter in systole), being higher in the heaviest group (10-12 kg), while the gender variable showed significant differences for LA (diameter of the left atrium) and LA/AO (ratio between LA and the diameter of the aorta), being greater in males. All the echocardiographic values for the three variables studied were within the expected range for the species.